Surface activated zinc-glutarate for the copolymerization of CO2 and epoxides - Yang, Yongmoon; Lee, Jong Doo; Seo, Yeong Hyun; Chae, Ju Hyung; Bang, Sohee; Cheong, Yeon Joo; Lee, Bun Yeoul; Lee, In Hwan; Son, Seung Uk; Jang, Hye Young (Dalton Transactions, 2022)
Zinc-glutarate (ZnGA) is a promising catalyst that can form polymers from CO2 and epoxides, thereby contributing to the development of CO2 utilization technologies and future sustainability. One of the obstacles to commercializing ZnGA in polymer industries is its low catalytic activity. In this study, we introduced activated two-dimensional (2D) ZnGA to improve its catalytic activity in polymerization. The morphology-controlled 2D ZnGA was treated with H3Co(CN)6, and a porous granular-type Co-modified ZnGA (Co-ZnGA) was prepared. The morphology of 2D ZnGA is a prerequisite for the activation by H3Co(CN)6. The catalytic properties of Co-ZnGA were evaluated by copolymerization of various epoxides and CO2, and exhibited catalytic activity of 855, 1540, 1190, and 148 g g-cat−1 with propylene oxide, 1,2-epoxyhexane, 1,2-epoxybutane, and styrene oxide, respectively. This study provided a new strategy using 2D ZnGA instead of conventional ZnGA for increasing the catalytic activity in CO2 polymerization.
Keywords: Catalytic properties; Copolymerisation; Morphology-controlled; Polymers industry; Propylene oxide; Styrene oxide; Two-dimensional; Zinc glutarate; ]+ catalyst